Fuel cell metal bipolar plate and fuel cell

By depositing a modified graphene and polyaniline/nanotitanium dioxide composite coating on the fuel cell metal bipolar plate, the problem of difficult to take into account the conductivity, corrosion resistance and hydrophobicity of the bipolar plate in humid environments is solved, and the performance and life of the fuel cell are significantly improved.

CN117117228BActive Publication Date: 2025-03-28GUANGDONG SIDA HYDROGEN ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311158520.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-28
Estimated Expiration
2043-09-08

AI Technical Summary

Technical Problem

It is difficult for existing fuel cell metal bipolar plates to take into account excellent conductivity, corrosion resistance and hydrophobicity at the same time, resulting in prone to "water flooding" failures when working in humid environments, affecting the performance and life of the fuel cell.

Method used

The modified graphene coating and the polyaniline/nanotitanium dioxide composite coating were deposited successively on the metal bipolar plate substrate by electrochemical methods. The modified graphene improved the hydrophobic properties by introducing fluorine atoms, and the polyaniline/nanotitanium dioxide composite coating enhanced the conductivity and corrosion resistance.

Benefits of technology

It realizes the high conductivity, good hydrophobicity and corrosion resistance of metal bipolar plates, avoids "water flooding" failures, and extends the service life of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004511913750000041
    Figure GDA0004511913750000041
  • Figure GDA0004511913750000131
    Figure GDA0004511913750000131
Patent Text Reader

Abstract

The present invention discloses a metal bipolar plate for a fuel cell, the metal bipolar plate comprising a metal bipolar plate substrate, a modified graphene coating and a polyaniline / nano-titanium dioxide composite coating; the modified graphene coating is deposited on the metal bipolar plate substrate, the polyaniline / nano-titanium dioxide composite coating is deposited on the modified graphene coating, and the modified graphene coating is a fluorinated graphene coating. The fluorinated graphene coating and the polyaniline / nano-titanium dioxide composite coating of the present application can play a synergistic role, while improving the hydrophobic properties of the metal bipolar plate, it also improves the electrical conductivity and corrosion resistance of its surface. At the same time, the present invention also provides a fuel cell comprising the above-mentioned metal bipolar plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a fuel cell metal bipolar plate and a fuel cell. Background Art

[0002] The main material of bipolar plates is graphite, which is expensive, making the cost of bipolar plate materials account for 25-35% of the total battery cost; in addition, graphite materials also have the defect of poor mechanical processing performance. Since metal materials have the advantages of low price, good mechanical processing performance, good toughness, and good strength, metal bipolar plates are considered by technicians in this field to be the inevitable choice for fuel cells.

[0003] Metal bipolar plates are an important part of hydrogen-oxygen fuel cells. Metal bipolar plates are used to isolate hydrogen from oxygen, and the airtightness of the battery must be ensured to prevent hydrogen and oxygen from communicating with each other and causing combustion or even explosion. At the same time, the battery current is collected through the bipolar plates and applied to the load, so the metal bipolar plates must have good density and conductivity. In addition to good density and conductivity, the water introduced and produced during the operation of the fuel cell is in the bipolar plate flow channel. If the excess water cannot be discharged in time, it will cause "flooding" in the metal bipolar plate flow channel, blocking the gas channel and causing the fuel cell system to stop working. Therefore, the metal bipolar plate needs to have good hydrophobic properties. Since the operating environment of the fuel cell usually contains F-, SO4 2- 、SO3 2 -CO3 2- 、HSO3 - Plasma aqueous solution and the operating temperature is generally 70-100℃. Metal materials are prone to corrosion or passivation in this fuel cell working environment, which leads to a decrease in battery performance. Therefore, metal bipolar plates also need to ensure good corrosion resistance. Achieving a reasonable match between the conductivity, hydrophobicity and corrosion resistance of metal bipolar plate materials, that is, achieving high corrosion resistance and hydrophobicity while ensuring reasonable conductivity, and ensuring the service life of the entire fuel cell system is one of the key links in the commercialization of fuel cells.

[0004] Conductive polymers such as polyaniline, polypyrrole, polythiophene, etc. have unique properties in terms of conductivity, electrochemical properties, mechanical strength, chemical and electrochemical synthesis, and are widely used in electrochemical sensors, capacitors, corrosion protection, etc. Among them, polyaniline has the advantages of good chemical stability, high conductivity, processability, easy polymerization, and low monomer cost, and can protect metals from corrosion by catalyzing the formation of a passivation oxide layer on the metal surface. It is a very promising metal protection material, but the surface of a single polyaniline coating prepared by electrodeposition often has micron-sized holes, which reduces the barrier effect on corrosive ions and weakens the durability of the polyaniline coating. Graphene is a carbon material with sp2 hybridized carbon atoms tightly stacked into a single-layer two-dimensional honeycomb lattice structure. Due to its unique electronic structure, it has extremely high thermal conductivity (3500W / mK) and electrical conductivity (106S / cm), and is theoretically impermeable to all molecules. It can simultaneously meet the performance requirements of electrical conductivity, thermal conductivity, and corrosion resistance. The composite of graphene and polyaniline can promote the delocalization of the π electrons of polyaniline, thereby improving the electrical conductivity and barrier properties of the graphene and polyaniline composite coating.

[0005] Chinese patent publication number 113675418A discloses a method for preparing a graphene conductive polymer coating on the surface of a bipolar plate by electrodeposition, comprising the following steps: step 1, chemically modifying graphene oxide, grafting anionic functional groups, and preparing a modified graphene oxide aqueous dispersion; step 2, mixing the modified graphene aqueous dispersion and the conductive polymer monomer aqueous dispersion in proportion to obtain an electrolyte; step 3, pretreating the metal-based bipolar plate, immersing the metal-based bipolar plate in a sulfuric acid solution, and removing the passivation film on its surface; step 4, using the metal-based bipolar plate as an anode and a platinum sheet as a cathode, and electro-depositing the metal-based bipolar plate with a DC power supply; step 5, drying the deposited wet film to obtain a graphene conductive polymer composite coating. Although this patent utilizes the doping effect of the functional groups on the surface of anionic modified graphene on the conductive polymer, which promotes the delocalization of π electrons in the conductive polymer and improves the conductivity of the composite coating; however, this patent does not improve the hydrophobic properties of the composite coating. If the metal bipolar plate coated with the composite coating works for a long time in a humid environment, it still cannot solve the problem of "flooding" in the flow channel of the metal bipolar plate during the operation of the fuel cell.

[0006] A Chinese patent with publication number CN112359328A discloses a method for surface treatment of a fuel cell bipolar plate, comprising the steps of: S1. cleaning the bipolar plate; S2. drying the cleaned bipolar plate; S3. preparing a nano-scale conductive hydrophobic layer on the surface of the dried bipolar plate; S4. roughening the bipolar plate after the nano-scale conductive hydrophobic layer is prepared to increase the roughness of the nano-scale conductive hydrophobic layer; this method only improves the hydrophobic properties of the bipolar plate surface, but does not improve the corrosion resistance and conductivity of the bipolar plate surface. Summary of the invention

[0007] In order to solve the deficiencies in the prior art, the purpose of the present invention is to provide a fuel cell metal bipolar plate and a fuel cell. The modified graphene coating and the polyaniline / nano-titanium dioxide composite coating are sequentially deposited on the metal bipolar plate substrate by an electrochemical method, thereby solving the problem that the metal bipolar plate in the prior art cannot simultaneously take into account excellent conductivity, corrosion resistance and hydrophobicity.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] A fuel cell metal bipolar plate, comprising a metal bipolar plate substrate, a modified graphene coating and a polyaniline / nano-titanium dioxide composite coating; the modified graphene coating is deposited on the metal bipolar plate substrate, the polyaniline / nano-titanium dioxide composite coating is deposited on the modified graphene coating, and the modified graphene coating is a fluorinated graphene coating.

[0010] Graphene is a new material with carbon atoms connected by sp2 hybridization tightly stacked into a single-layer two-dimensional honeycomb lattice structure. Due to its special single-atom layer structure, it has unique physical properties, such as high strength, high modulus, high thermal conductivity, high electron mobility, high specific surface area and high barrier properties, which makes it have important application prospects in conductive materials. However, existing graphene materials are difficult to meet the requirements of working for a long time in a humid environment. A fuel cell is a power generation device that converts hydrogen oxidative energy into electrical energy. In a fuel cell, hydrogen and oxygen react to generate electricity while also generating liquid water. In general, excessive reaction gas is introduced, and the unreacted gas will carry away the generated liquid water. However, if the gas is insufficient, it will cause a "flooding" failure in the flow channel of the metal bipolar plate, blocking the gas channel and causing the fuel cell system to stop working. Therefore, the surface of the metal bipolar plate needs to have good hydrophobicity. The present application deposits a modified graphene coating on the surface of a metal bipolar plate, introduces fluorine atoms into the modified graphene to replace the carboxyl groups at the ends of graphene oxide, thereby obtaining fluorinated graphene oxide, and then uses a reducing agent to reduce the fluorinated graphene oxide to obtain fluorinated graphene; the introduction of fluorine atoms greatly reduces the surface energy of graphene, thereby improving the hydrophobic properties of fluorinated graphene.

[0011] Preferably, the method for preparing the metal bipolar plate comprises the following steps:

[0012] Step S1, using the substrate of the metal bipolar plate as the working electrode, the saturated calomel electrode as the reference electrode, the platinum electrode as the auxiliary electrode, and the fluorinated graphene suspension as the electrolyte, depositing the fluorinated graphene coating on the surface of the metal bipolar plate substrate by an electrochemical method;

[0013] Step S2: using a polyaniline / nano-titanium dioxide suspension as an electrolyte, using a substrate of a metal bipolar plate on which the fluorinated graphene coating is deposited as a working electrode, and adopting a three-electrode system to in-situ deposit the polyaniline / nano-titanium dioxide composite coating on the surface of the fluorinated graphene coating by an electrochemical method.

[0014] Preferably, the method for preparing the metal bipolar plate further comprises pre-treating the surface of the metal bipolar plate substrate; the pre-treatment comprises grinding, polishing, cleaning, ion sputtering and surface etching in sequence.

[0015] Grinding, polishing and cleaning the surface of the metal bipolar plate substrate can improve the cleanliness and roughness of the metal substrate, increase the specific surface area of ​​the metal substrate, and thus enhance the bonding force between the metal substrate and the coating; in order to ensure that the oxides or other impurities on the surface of the metal bipolar plate substrate can be removed completely, the surface of the bipolar plate substrate is ion sputtered and surface etched. At the same time, ion sputtering and surface etching can further improve the roughness of the metal substrate surface, increase the surface area, and enhance the bonding force between the metal bipolar plate substrate and the coating.

[0016] Preferably, the preparation method of the fluorinated graphene coating in step S1 is as follows:

[0017] (1) adding graphene oxide to an N-methylpyrrolidone solution and ultrasonically dispersing the solution to obtain a graphene oxide dispersion;

[0018] (2) adding an alkaline agent, a photocatalyst and a fluorination agent to the graphene oxide dispersion obtained in step (1) in sequence, mixing and stirring evenly, reacting under light conditions, filtering, washing, and vacuum freeze-drying to obtain fluorinated graphene oxide; the specific reaction formula is as follows:

[0019]

[0020] (3) adding the fluorinated graphene oxide obtained in step (2) into deionized water for ultrasonic dispersion, adding a reducing agent, hydrazine hydrate, continuing ultrasonic mixing, reacting fully under stirring conditions, filtering, washing, and vacuum drying to obtain a fluorinated graphene coating.

[0021] Preferably, the mass percentage of graphene oxide solids in the graphene oxide dispersion in step (1) is 1%-2%; the mass ratio of the alkaline agent, the photocatalyst, the fluorination agent and the graphene oxide in step (2) is (0.01-0.2): (0.01-0.06): (0.8-4): 1, wherein the alkaline agent is potassium hydroxide or dipotassium hydrogen phosphate, the photocatalyst is at least one of [Ru(bpy)3](PF6)2, Ir(ppy)2(dtbbpy)(PF6) or Cr(phen)3(PF6)3, and the fluorination agent is N-fluoro At least one of dibenzenesulfonamide or 1-fluoropyridine trifluoromethanesulfonate, the conditions for the light irradiation reaction are: irradiation with a light source of 300-600nm; the reaction time is 4-8h; the vacuum freeze drying temperature is (-40)-(-20)°C, and the vacuum freeze drying time is 48-72h; the mass ratio of fluorinated graphene oxide, deionized water and hydrazine hydrate in step (3) is 1:100:(0.8-1), the stirring reaction conditions are: reaction at 80-90°C water bath conditions for 80-120min, vacuum drying temperature is 70-90°C, and the time is 3-8h.

[0022] This application uses transition metal photosensitizer complex catalysts. Compared with traditional photocatalysts, transition metal photosensitizer complex catalysts can be easily excited within the visible light wavelength range, reducing the threshold of chemical reactions, thereby activating the high-potential fluorinating agent N-fluorodibenzenesulfonamide or 1-fluoropyridine trifluoromethanesulfonate. The activated fluorinating agent can easily attack the carboxyl group at the end of graphene, remove a molecule of -CO2, form a CF ion bond, and obtain fluorinated graphene oxide. The fluorinated graphene oxide is then reduced to obtain fluorinated graphene; the CF ion bond can further enhance the conductivity of fluorinated graphene, and the introduction of fluorine reduces the surface energy of graphene, thereby improving the hydrophobicity of fluorinated graphene. Compared with organic small molecule photosensitive catalysts, transition metal photosensitizer complex catalysts have a higher efficiency in absorbing light and can prompt the reaction to be completed faster.

[0023] Preferably, the power of ultrasonic dispersion in steps (1) and (3) is 80-100 W and the time is 5-10 h.

[0024] Preferably, the preparation method of the polyaniline / nano-titanium dioxide composite coating in step S2 adopts a three-electrode system through cyclic voltammetry, and the specific steps are as follows: a nano-titanium dioxide sample is used as a working electrode, a Pt sheet is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and the electrolyte is an ethanol solution containing 0.1M aniline and 0.5M oxalic acid, and the scanning speed is 50mV / s and circulated 20-40 times in the range of -0.4-1.2V to deposit polyaniline on the surface of the nano-titanium dioxide working electrode sheet, and then the sample is rinsed with ethanol and deionized water, dried, and dried at 80-100°C for 2-4h to obtain the polyaniline / nano-titanium dioxide composite coating.

[0025] In order to ensure the conductivity of the polyaniline / nano-titanium dioxide composite coating, the mass percentage of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating is 5-15.

[0026] Polyaniline has the advantages of good chemical stability, high conductivity, processability, easy polymerization and low monomer cost. In recent years, with the development of fuel cells, it has become an important material for bipolar plate protection. However, the polyaniline coating synthesized by electrochemical synthesis in the prior art has certain defects in its interface contact resistance and surface, which will reduce the conductivity and corrosion resistance of the polyaniline coating. Therefore, the long-term corrosion resistance of the single polyaniline coating in the high temperature and strong acid working environment of the fuel cell still cannot meet the requirements. The present application prepares an aniline / nano-titanium dioxide composite coating by introducing titanium dioxide nanoparticles. Since the titanium dioxide nanoparticles are small in size, they can fill the pores in the polyaniline coating, reduce the diffusion of corrosion ions in the gaps, and provide a physical barrier for external corrosion ions. Therefore, in a strong acid corrosion environment, the titanium dioxide nanoparticles can significantly reduce the porosity of the polyaniline coating, improve the defects on the surface of the polyaniline coating, and reduce the interface resistance of the polyaniline coating, thereby increasing the conductivity of the polyaniline coating; at the same time, the conductive polymer polyaniline is p-type and titanium dioxide is an n-type semiconductor. The two substances can form a pn junction to prevent the transmission of charges between the polyaniline coatings, thereby enhancing the corrosion resistance of the polyaniline.

[0027] Due to the characteristics of titanium dioxide semiconductor, when the content of titanium dioxide nanoparticles is too high, the conductive path of the polyaniline matrix will be blocked, thereby reducing the conductive performance of the polyaniline coating itself. The applicant of the present invention has concluded through a large number of experimental studies that when the mass percentage of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating is 5%-15%, the conductivity of the polyaniline / nano-titanium dioxide composite coating will increase with the increase of the titanium dioxide content; when the titanium dioxide content exceeds 15%, the conductivity of the polyaniline / nano-titanium dioxide composite coating will decrease with the increase of the titanium dioxide content; when the titanium dioxide content is lower than 5%, the surface pore defects of the polyaniline coating cannot be completely and effectively improved due to the low titanium dioxide content, resulting in a significant decrease in the conductivity of the polyaniline / nano-titanium dioxide composite coating, which may even be lower than the conductivity of the polyaniline coating itself.

[0028] Preferably, the electrochemical method in step S2 is cyclic voltammetry, and the conditions of the cyclic voltammetry are as follows: the scanning range is controlled to be -0.2-1.2V, the scanning speed is 50mV / s, and the number of cycles is 20-40 times.

[0029] Preferably, a fuel cell comprises the above-mentioned metal bipolar plate,

[0030] Further preferably, the fuel cell is a hydrogen-oxygen fuel cell.

[0031] Compared with the prior art, the present invention has the following positive and beneficial effects:

[0032] The present invention deposits a layer of fluorinated graphene on the surface of the metal bipolar plate substrate by an electrochemical method, introduces fluorine atoms into the graphene, forms a CF ion bond, and because the C and F ions in the CF ion bond can move freely, the conductivity of the fluorinated graphene is enhanced, and the introduction of fluorine reduces the surface energy of the graphene, thereby improving the hydrophobicity of the fluorinated graphene; the fluorinated graphene is deposited on the surface of the metal bipolar plate substrate by an electrochemical method, and because the fluorinated graphene has good hydrophobicity, it can well repel water molecules, thereby solving the problem of "flooding" in the flow channel of the metal bipolar plate, allowing water molecules to be able to stay away from the metal bipolar plate substrate and the polyaniline / nano-titanium dioxide composite coating in time, preventing water molecules from further corroding the metal bipolar plate substrate, thereby improving The corrosion resistance of the metal bipolar plate is improved; water molecules are kept away from the polyaniline / nano-titanium dioxide composite coating, which can increase the bonding force between the fluorinated graphene coating and the polyaniline / nano-titanium dioxide composite coating, reduce the interface resistance between the fluorinated graphene coating and the polyaniline / nano-titanium dioxide composite coating, thereby increasing the conductivity of the polyaniline / nano-titanium dioxide composite coating; at the same time, the polyaniline / nano-titanium dioxide composite coating is deposited on the fluorinated graphene coating, and the polyaniline / nano-titanium dioxide composite coating can be used as a covering layer to cover and repair the defects on the surface of the fluorinated graphene coating, reduce the defect density of the fluorinated graphene surface coating, and improve the shielding effect of the fluorinated graphene coating on the corrosive ions, thereby improving the corrosion resistance of the fluorinated graphene coating. It can be seen that after the fluorinated graphene coating and the polyaniline / nano-titanium dioxide composite coating are deposited on the metal bipolar plate substrate in sequence, the fluorinated graphene coating and the polyaniline / nano-titanium dioxide composite coating can play a synergistic role, while improving the hydrophobicity of the metal bipolar plate, it also improves the conductivity and corrosion resistance of its surface. DETAILED DESCRIPTION

[0033] The technical solutions in this application will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used were not specified by manufacturer and are all commercially available conventional products.

[0035] Example 1

[0036] A fuel cell metal bipolar plate comprises a metal bipolar plate substrate, a modified graphene coating and a polyaniline / nano-titanium dioxide composite coating; the material of the metal bipolar plate substrate is 316L stainless steel, and the modified graphene coating and the polyaniline / nano-titanium dioxide composite coating are sequentially deposited on the 316L stainless steel substrate by an electrochemical method. The steps of preparing the metal bipolar plate are as follows:

[0037] (1) First, 1 g of commercially available graphene oxide (Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the following examples and comparative examples also use the same graphene oxide) was added to 99 g of N-methylpyrrolidone solution for ultrasonic dispersion at a power of 80 W for 10 h to obtain a graphene oxide dispersion with a mass fraction of 1%. Then, 0.01 g of potassium hydroxide, 0.01 g of [Ru(bpy)3](PF6)2, and 0.8 g of N-fluorocarbon were added to 100 g of the obtained graphene oxide dispersion with a mass fraction of 1%. dibenzenesulfonamide, mix and stir evenly, react under 300nm light source for 8h, filter, wash, and vacuum freeze-dry at -20℃ for 72h to obtain fluorinated graphene oxide; finally, add 1g of the obtained fluorinated graphene oxide to 100g deionized water for ultrasonic dispersion, the ultrasonic dispersion power is 80W, the ultrasonic time is 10h, add 0.8g of reducing agent hydrazine hydrate, continue to ultrasonically mix evenly, stir and react in a water bath at 80℃ for 120min, filter and wash after the reaction is completed, and vacuum dry at 70℃ for 8h to obtain fluorinated graphene for standby use.

[0038] (2) The surface of the 316L stainless steel substrate is sequentially ground, polished, and cleaned.

[0039] Specifically, first, the surface of the 316L stainless steel substrate is polished with 2000# SiC sandpaper; then, the substrate is polished with a brightener such as alumina polishing paste or diamond polishing paste, on the one hand, to remove the oxide scale on the surface of the metal bipolar plate substrate, and on the other hand, the texture and defects on the surface of the metal bipolar plate substrate are reduced by polishing to improve the flatness of the material; then, the polished metal bipolar plate substrate is rinsed with deionized water, and then the metal bipolar plate is immersed in ethanol and acetone solutions for ultrasonic cleaning for 30 minutes each, and then dried. The pretreatment of the metal bipolar plate substrate by grinding, polishing, cleaning, etc. can improve the cleanliness and roughness of the metal bipolar plate substrate, increase the specific surface area of ​​the metal bipolar plate substrate, thereby enhancing the bonding force between the metal bipolar plate substrate and the coating, reducing the interface resistance between the metal bipolar plate substrate and the coating, and improving the conductivity of the bipolar plate.

[0040] (3) Place the metal bipolar plate treated in step (2) into the vacuum chamber of the biased magnetron sputtering device and evacuate the chamber to a vacuum degree of 5×10-3 Pa, and heat the metal bipolar plate to 160°C, introduce argon gas at a pressure of about 1Pa, and set the bias voltage to -220V; perform surface ion sputtering and etching activation on the metal bipolar plate, and the time is controlled within 15 minutes.

[0041] By ion sputtering and etching the surface of the metal bipolar plate substrate, oxides or other impurities on the surface of the metal bipolar plate substrate can be removed. At the same time, the roughness of the metal substrate surface can be further improved, its surface area can be increased, the bonding force between the metal bipolar plate substrate and the coating can be strengthened, the interface resistance between the metal bipolar plate substrate and the coating can be reduced, and the conductivity of the metal bipolar plate can be improved.

[0042] (4) 0.005 g of fluorinated graphene solid was added to 1 L of deionized water to prepare a 5 mg / L fluorinated graphene suspension, which was used as an electrolyte for electrochemical deposition, with the treated 316L stainless steel substrate as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the auxiliary electrode. The deposition method adopted cyclic voltammetry with a voltage range of -0.2-1.2 V, a scan speed of 50 mV / s, and 20 cycles to prepare a fluorinated graphene coating.

[0043] (5) 9.3 g of aniline monomer and 45 g of oxalic acid were placed in 1 L of ethanol solution to prepare an ethanol solution containing 0.1 M aniline and 0.5 M oxalic acid, and this was used as an electrolyte for electrochemical deposition, with a sample of titanium dioxide nanoparticles as a working electrode, a Pt sheet as a counter electrode, and a saturated calomel electrode as a reference electrode. The scanning speed was 50 mV / s and the cycle was repeated 20 times in the range of -0.4-1.2 V to deposit polyaniline on the surface of the nano-titanium dioxide working electrode sheet. The sample was then rinsed with ethanol and deionized water, dried, and dried at 80°C for 4 h to obtain a polyaniline / nano-titanium dioxide coating.

[0044] (6) Sodium dodecylbenzene sulfonate was first added to 1 L of deionized water, and then 5 g of polyaniline / nano-titanium dioxide composite was added to obtain a polyaniline / nano-titanium dioxide suspension. The purpose of adding sodium dodecylbenzene sulfonate was to improve the dispersibility and stability of the polyaniline / nano-titanium dioxide suspension. The polyaniline / nano-titanium dioxide suspension was used as an electrolyte, and a three-electrode system was adopted. A 316L stainless steel substrate of a metal bipolar plate with a fluorinated graphene coating was deposited as a working electrode, a saturated calomel electrode was used as a reference electrode, and a platinum electrode was used as an auxiliary electrode. The scanning speed was 50 mV / s and the reaction was cycled 20 times in the range of -0.2-1.2 V to in-situ deposit the polyaniline / nano-titanium dioxide composite coating on the surface of the fluorinated graphene coating.

[0045] (7) The working electrode is taken out from the electrolyte, the surface of the metal bipolar plate is cleaned with flowing deionized water, and then dried in a vacuum to obtain a metal bipolar plate having a fluorinated graphene-polyaniline / nano-titanium dioxide composite coating on the surface.

[0046] In this embodiment, the mass percentage of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating is 5%.

[0047] Example 2

[0048] (1) First, 1.5 g of commercially available graphene oxide (name of the purchasing company, the same below) was added to 98.5 g of N-methylpyrrolidone solution for ultrasonic dispersion at a power of 90 W and an ultrasonic time of 7 h to obtain a graphene oxide dispersion with a mass fraction of 1.5%; then, 0.15 g of dipotassium hydrogen phosphate, 0.06 g of Ir(ppy)2(dtbbpy)(PF6) and 3 g of 1-fluoropyridine trifluoromethanesulfonic acid, mix and stir evenly, react under 500nm light source for 6h, filter, wash, and vacuum freeze-dry at -30℃ for 60h to obtain fluorinated graphene oxide; finally, add 1g of the obtained fluorinated graphene oxide to 100g of deionized water for ultrasonic dispersion, the ultrasonic dispersion power is 90W, the ultrasonic time is 7h, 0.9g of reducing agent hydrazine hydrate is added, and ultrasonic mixing is continued to be uniform, and the reaction is stirred in a water bath at 85℃ for 100min. After the reaction is completed, filter and wash, and vacuum dry at 80℃ for 5h to obtain fluorinated graphene for standby use.

[0049] (2) The surface of the 316L stainless steel substrate is sequentially ground, polished, and cleaned.

[0050] (3) Place the metal bipolar plate treated in step (2) into the vacuum chamber of the biased magnetron sputtering device and evacuate the chamber to a vacuum degree of 5×10 -3 Pa, and heat the metal bipolar plate to 160°C, introduce argon gas at a pressure of about 1Pa, and set the bias voltage to -220V; perform surface ion sputtering and etching activation on the metal bipolar plate, and the time is controlled within 15 minutes.

[0051] (4) 0.005 g of fluorinated graphene solid was added to 1 L of deionized water to prepare a 5 mg / L fluorinated graphene suspension, which was used as an electrolyte for electrochemical deposition, with the treated 316L stainless steel substrate as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the auxiliary electrode. The deposition method adopted cyclic voltammetry with a voltage range of -0.2-1.2 V, a scan speed of 50 mV / s, and 30 cycles to prepare a fluorinated graphene coating.

[0052] (5) 9.3 g of aniline monomer and 45 g of oxalic acid were placed in 1 L of ethanol solution to prepare an ethanol solution containing 0.1 M aniline and 0.5 M oxalic acid, and the solution was used as an electrolyte for electrochemical deposition. The titanium dioxide nanoparticle sample was used as the working electrode, the Pt sheet was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode. The scanning speed was 50 mV / s and the cycle was repeated 30 times in the range of -0.4-1.2 V to deposit polyaniline on the surface of the nano-titanium dioxide working electrode sheet. The sample was then rinsed with ethanol and deionized water, dried, and dried at 90°C for 3 h to obtain a polyaniline / nano-titanium dioxide coating.

[0053] (6) Sodium dodecylbenzene sulfonate was first added to 1 L of deionized water, and then 5 g of polyaniline / nano-titanium dioxide composite was added to obtain a polyaniline / nano-titanium dioxide suspension. The purpose of adding sodium dodecylbenzene sulfonate was to improve the dispersibility and stability of the polyaniline / nano-titanium dioxide suspension. The polyaniline / nano-titanium dioxide suspension was used as an electrolyte, and a three-electrode system was adopted. A 316L stainless steel substrate of a metal bipolar plate with a fluorinated graphene coating was deposited as a working electrode, a saturated calomel electrode was used as a reference electrode, and a platinum electrode was used as an auxiliary electrode. The scanning speed was 50 mV / s and the reaction was cycled 30 times in the range of -0.2-1.2 V to in-situ deposit the polyaniline / nano-titanium dioxide composite coating on the surface of the fluorinated graphene coating.

[0054] (7) The working electrode is taken out from the electrolyte, the surface of the metal bipolar plate is cleaned with flowing deionized water, and then dried in a vacuum to obtain a metal bipolar plate having a fluorinated graphene-polyaniline / nano-titanium dioxide composite coating on the surface.

[0055] In this embodiment, the mass percentage of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating is 10%.

[0056] Example 3

[0057] (1) First, 2 g of commercially available graphene oxide (name of the purchasing company, the same below) was added to 98 g of N-methylpyrrolidone solution for ultrasonic dispersion at a power of 100 W and an ultrasonic time of 5 h to obtain a graphene oxide dispersion with a mass fraction of 2%; then, 0.4 g of potassium hydroxide, 0.12 g of Cr(phen)3(PF6)3 and 8 g of N-fluorodibenzenesulfonamide, mix and stir evenly, react under 600nm light source for 4h, filter, wash, and vacuum freeze-dry at -40℃ for 48h to obtain fluorinated graphene oxide; finally, add 1g of the obtained fluorinated graphene oxide to 100g deionized water for ultrasonic dispersion, the ultrasonic dispersion power is 100W, the ultrasonic time is 5h, add 1g of reducing agent hydrazine hydrate, continue to ultrasonically mix evenly, stir and react in a 90℃ water bath for 80min, filter and wash after the reaction is completed, and vacuum dry at 90℃ for 3h to obtain fluorinated graphene for standby use.

[0058] (2) The surface of the 316L stainless steel substrate is sequentially ground, polished, and cleaned.

[0059] (3) Place the metal bipolar plate treated in step (2) into the vacuum chamber of the biased magnetron sputtering device and evacuate the chamber to a vacuum degree of 5×10 -3 Pa, and heat the metal bipolar plate to 160°C, introduce argon gas at a pressure of about 1Pa, and set the bias voltage to -220V; perform surface ion sputtering and etching activation on the metal bipolar plate, and the time is controlled within 15 minutes.

[0060] (4) 0.005 g of fluorinated graphene solid was added to 1 L of deionized water to prepare a 5 mg / L fluorinated graphene suspension, which was used as an electrolyte for electrochemical deposition, with the treated 316L stainless steel substrate as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the auxiliary electrode. The deposition method adopted cyclic voltammetry with a voltage range of -0.2-1.2 V, a scan speed of 50 mV / s, and 40 cycles to prepare a fluorinated graphene coating.

[0061] (5) 9.3 g of aniline monomer and 45 g of oxalic acid were placed in 1 L of ethanol solution to prepare an ethanol solution containing 0.1 M aniline and 0.5 M oxalic acid, and the solution was used as an electrolyte for electrochemical deposition. The titanium dioxide nanoparticle sample was used as the working electrode, the Pt sheet was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode. The scanning speed was 50 mV / s and the cycle was repeated 40 times in the range of -0.4-1.2 V to deposit polyaniline on the surface of the nano-titanium dioxide working electrode sheet. The sample was then rinsed with ethanol and deionized water, dried, and dried at 100°C for 2 h to obtain a polyaniline / nano-titanium dioxide coating.

[0062] (6) Sodium dodecylbenzene sulfonate was first added to 1 L of deionized water, and then 5 g of polyaniline / nano-titanium dioxide composite was added to obtain a polyaniline / nano-titanium dioxide suspension. The purpose of adding sodium dodecylbenzene sulfonate was to improve the dispersibility and stability of the polyaniline / nano-titanium dioxide suspension. The polyaniline / nano-titanium dioxide suspension was used as an electrolyte, and a three-electrode system was adopted. A 316L stainless steel substrate of a metal bipolar plate with a fluorinated graphene coating was deposited as a working electrode, a saturated calomel electrode was used as a reference electrode, and a platinum electrode was used as an auxiliary electrode. The scanning speed was 50 mV / s and the reaction was cycled 40 times in the range of -0.2-1.2 V to in-situ deposit the polyaniline / nano-titanium dioxide composite coating on the surface of the fluorinated graphene coating.

[0063] (7) The working electrode is taken out from the electrolyte, the surface of the metal bipolar plate is cleaned with flowing deionized water, and then dried in a vacuum to obtain a metal bipolar plate having a fluorinated graphene-polyaniline / nano-titanium dioxide composite coating on the surface.

[0064] In this embodiment, the mass percentage of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating is 15%.

[0065] Comparative Example 1

[0066] In this comparative example 1, the fluorinated graphene is replaced with an equal amount of graphene, and the step of fluorinating the graphene oxide is omitted. The other steps are the same as those in Example 3.

[0067] Comparative Example 2

[0068] In this comparative example 2, the mass percentage of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating was adjusted to 4%, and the other steps were the same as those in example 3.

[0069] Comparative Example 3

[0070] In this comparative example 3, the mass percentage of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating was adjusted to 16%, and the other steps were the same as those in Example 3.

[0071] Comparative Example 4

[0072] In this comparative example 4, the polyaniline / nano-titanium dioxide composite coating is replaced by an equal amount of polyaniline coating, and the other steps are the same as those in Example 3; the preparation method of the polyaniline coating is as follows:

[0073] 9.3 g of aniline monomer and 45 g of oxalic acid were placed in 1 L of ethanol solution to prepare an ethanol solution containing 0.1 M aniline and 0.5 M oxalic acid, which was used as an electrolyte for electrochemical deposition, with a 316L stainless steel electrode as the working electrode, a Pt sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. The scanning speed was 50 mV / s and the cycle was repeated 40 times in the range of -0.4-1.2 V to deposit polyaniline on the surface of the nano-titanium dioxide working electrode sheet. The sample was then rinsed with ethanol and deionized water, dried, and dried at 100°C for 2 hours to obtain a polyaniline coating.

[0074] The metal bipolar plate samples prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, and the test results are shown in Table 1. The corrosion current and corrosion potential were measured by potential scanning, with a scanning rate of 1 mV / s and a potential scanning range of -0.3V-1.5V; the contact resistance was the result of testing under a pressure of 1.4 MPa (at present, the assembly force of hydrogen and oxygen fuel cell stacks is usually around 1.4 MPa); the coating adhesion was obtained by a scratch test using the national safety standard JB / T8554-1997; the water contact angle of different fluorinated graphene or graphene films was measured by a contact angle meter (DSA100, KRUSS, Germany) to evaluate the hydrophobicity of the film, with a water droplet of 5 μL each time, and each sample was tested 3 times to take the average value to ensure the accuracy of the results.

[0075] Table 1 Performance test data of metal bipolar plates prepared in Examples 1-3 and Comparative Examples 1-4

[0076]

[0077] It can be seen from the data in Table 1 that the embodiment of the present invention can significantly improve the hydrophobicity, electrical conductivity and corrosion resistance of the metal bipolar plate by depositing the fluorinated graphene coating and the polyaniline / nano-titanium dioxide composite coating on the metal bipolar plate. This is mainly due to: introducing fluorine atoms into graphene to form CF ion bonds. Since the C and F ions in the CF ion bonds can move freely, the conductivity of the fluorinated graphene is enhanced. In addition, the introduction of fluorine reduces the surface energy of the graphene and increases the hydrophobicity of the fluorinated graphene. Since the fluorinated graphene has good hydrophobicity, it can repel water molecules well, solving the problem of "flooding" in the flow channel of the metal bipolar plate, allowing water molecules to stay away from the metal bipolar plate substrate and the polyaniline / nano-titanium dioxide composite coating in time, preventing water molecules from further corroding the metal bipolar plate. The substrate of the plate, thereby improving the corrosion resistance of the metal bipolar plate; water molecules away from the polyaniline / nano-titanium dioxide composite coating can also increase the bonding force between the fluorinated graphene coating and the polyaniline / nano-titanium dioxide composite coating, reduce the interface resistance between the fluorinated graphene coating and the polyaniline / nano-titanium dioxide composite coating, thereby increasing the conductivity between the polyaniline / nano-titanium dioxide composite coating and the fluorinated graphene coating; at the same time, the polyaniline / nano-titanium dioxide composite coating is deposited on the fluorinated graphene coating, and the polyaniline / nano-titanium dioxide composite coating can be used as a covering layer to cover and repair the defects on the surface of the fluorinated graphene coating, reduce the defect density of the fluorinated graphene surface coating, and improve the shielding effect of the fluorinated graphene coating on the corrosive ions, thereby improving the corrosion resistance of the fluorinated graphene coating. It can be seen that the fluorinated graphene coating and the polyaniline / nano-titanium dioxide composite coating can play a synergistic role, while improving the hydrophobicity of the metal bipolar plate, it also improves the conductivity and corrosion resistance of its surface.

[0078] The comparison between Comparative Example 1 and Example 3 shows that due to the lack of introduction of fluorine atoms, the hydrophobicity of graphene decreases, which leads to a decrease in the corrosion resistance and conductivity of the graphene coating, thereby affecting the corrosion resistance and conductivity of the metal bipolar plate.

[0079] From the comparison between Comparative Example 2 and Example 3, it can be seen that: since the content of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating is too low, the titanium dioxide nanoparticles cannot completely and effectively improve the pore defects on the surface of the polyaniline coating, resulting in a significant decrease in the conductivity of the polyaniline / nano-titanium dioxide composite coating, and ultimately a decrease in the conductivity of the metal bipolar plate.

[0080] From the comparison between Comparative Example 3 and Example 3, it can be seen that since the content of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating is too high, the excessive content of titanium dioxide nanoparticles may block the conductive path of the polyaniline matrix, thereby reducing the conductive properties of the polyaniline coating itself, and ultimately reducing the conductivity of the metal bipolar plate.

[0081] Comparison of Comparative Example 4 with Example 3 shows that: due to the presence of certain defects in the interface contact resistance and the surface of the electrochemically synthesized polyaniline coating, the conductivity and corrosion resistance of the polyaniline coating are greatly reduced. The present application prepares an aniline / nano-titanium dioxide composite coating by introducing titanium dioxide nanoparticles. Since the titanium dioxide nanoparticles are small in size, they can fill the pores in the polyaniline coating, reduce the diffusion of corrosive ions in the gaps, and provide a physical barrier to external corrosive ions. Therefore, in a strong acid corrosion environment, the titanium dioxide nanoparticles can significantly reduce the porosity of the polyaniline coating, improve the defects on the surface of the polyaniline coating, and reduce the interface resistance of the polyaniline coating, thereby increasing the conductivity of the polyaniline coating; at the same time, the conductive polymer polyaniline is p-type, and titanium dioxide is an n-type semiconductor. Both substances can form a pn junction to prevent the transmission of charges between the polyaniline coatings, thereby enhancing the corrosion resistance of the polyaniline coating.

[0082] The comparison between Comparative Examples 2-4 and Example 3 shows that the introduction of titanium dioxide can increase the conductivity and corrosion resistance of the polyaniline coating to a certain extent, thereby improving the conductivity and corrosion resistance of the metal bipolar plate, and further extending the service life of the hydrogen-oxygen fuel cell.

[0083] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A fuel cell metal bipolar plate, characterized in that: The metal bipolar plate comprises a metal bipolar plate substrate, a modified graphene coating and a polyaniline / nano-titanium dioxide composite coating; the modified graphene coating is deposited on the metal bipolar plate substrate, the polyaniline / nano-titanium dioxide composite coating is deposited on the modified graphene coating, and the modified graphene coating is a fluorinated graphene coating; The method for preparing the metal bipolar plate comprises the following steps: Step S1, using the substrate of the metal bipolar plate as the working electrode, the saturated calomel electrode as the reference electrode, the platinum electrode as the auxiliary electrode, and the fluorinated graphene suspension as the electrolyte, depositing the fluorinated graphene coating on the surface of the metal bipolar plate substrate by an electrochemical method; Step S2, first adding sodium dodecylbenzene sulfonate to deionized water, and then adding a polyaniline / nano-titanium dioxide composite to obtain a polyaniline / nano-titanium dioxide suspension, using the polyaniline / nano-titanium dioxide suspension as an electrolyte, using the substrate of the metal bipolar plate deposited with the fluorinated graphene coating as a working electrode, and using a three-electrode system to in-situ deposit the polyaniline / nano-titanium dioxide composite coating on the surface of the fluorinated graphene coating by an electrochemical method; Wherein, the preparation method of the polyaniline / nano-titanium dioxide composite coating in step S2 adopts a three-electrode system through cyclic voltammetry, and the specific steps are as follows: a sample of titanium dioxide nanoparticles is used as a working electrode, a Pt sheet is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and the polyelectrolyte is an ethanol solution containing 0.1M aniline and 0.5M oxalic acid, and the polyaniline is deposited on the surface of the nano-titanium dioxide working electrode sheet at a scanning speed of 50mV / s in the range of -0.4-1.2V for 20-40 times, and the sample is then rinsed with ethanol and deionized water, dried, and dried at 80-100°C for 2-4 hours to obtain a polyaniline / nano-titanium dioxide composite coating; The electrochemical method in step S2 is cyclic voltammetry, and the conditions of the cyclic voltammetry are as follows: the scanning range is controlled to be -0.2-1.2V, the scanning speed is 50mV / s, and the number of cycles is 20-40 times; The mass percentage of titanium dioxide in the polyaniline / nano-titanium dioxide composite coating is 5-15%.

2. A fuel cell metal bipolar plate according to claim 1, characterized in that: The method for preparing the metal bipolar plate also includes pre-treating the surface of the metal bipolar plate substrate; the pre-treatment includes grinding, polishing, cleaning, ion sputtering, and surface etching in sequence.

3. A fuel cell metal bipolar plate according to claim 1, characterized in that: The preparation method of the fluorinated graphene coating in step S1 is as follows: (1) adding graphene oxide to an N-methylpyrrolidone solution for ultrasonic dispersion to obtain a graphene oxide dispersion; (2) adding an alkaline agent, a photocatalyst and a fluorination agent to the graphene oxide dispersion obtained in step (1) in sequence, mixing and stirring evenly, reacting under light conditions, filtering, washing and vacuum freeze-drying to obtain a fluorinated graphene oxide coating; (3) The fluorinated graphene oxide obtained in step (2) is added to deionized water for ultrasonic dispersion, and a reducing agent, hydrazine hydrate, is added, and ultrasonic mixing is continued to be uniform. The mixture is fully reacted under stirring conditions, filtered, washed, and vacuum dried to obtain fluorinated graphene.

4. A fuel cell metal bipolar plate according to claim 3, characterized in that: In the step (1), the mass percentage of graphene oxide solids in the graphene oxide dispersion is 1-2%; in the step (2), the mass ratio of the alkaline agent, the photocatalyst, the fluorination agent and the graphene oxide is (0.01-0.2): (0.01-0.06): (0.8-4): 1, wherein the alkaline agent is potassium hydroxide or dipotassium hydrogen phosphate, the photocatalyst is at least one of [Ru(bpy)3](PF6)2, Ir(ppy)2(dtbbpy)(PF6) or Cr(phen)3(PF6)3, and the fluorination agent is N-fluorodiphenyl At least one of sulfonamide or 1-fluoropyridine trifluoromethanesulfonate, the conditions for the light irradiation reaction are: irradiation with a light source of 300-600nm; the reaction time is 4-8h; the vacuum freeze drying temperature is (-40)-(-20)℃, and the vacuum freeze drying time is 48-72h; the mass ratio of fluorinated graphene oxide, deionized water and hydrazine hydrate in step (3) is 1:100:(0.8-1), the stirring reaction conditions are: reaction at 80-90℃ water bath conditions for 80-120min, vacuum drying temperature is 70-90℃, and the time is 3-8h.

5. A fuel cell metal bipolar plate according to claim 3, characterized in that: The power of ultrasonic dispersion in steps (1) and (3) is 80-100 W and the time is 5-10 h.

6. A fuel cell, characterized in that: The fuel cell comprises the metal bipolar plate according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Surface treatment method for bipolar plate of fuel cell

    CN112359328A

  • Method for preparing graphene conductive polymer coating on surface of bipolar plate by adopting electro-deposition process

    CN113675418A

  • Preparation and application of graphene / substrate electrode and polyaniline-graphene / substrate electrode

    CN102760888A

  • Hydrophobic graphene conductive material and preparation method of composite film of hydrophobic graphene conductive material

    CN114348995A